Six Sigma Approach to Control the Quality of Tablet (Case Study: Pharmaceutical Company) - Amanah Pasaribu, ST, MM (Journal of Management and Leadership, 2018)
Quality of product is one of the competitive advantages for the company. Pharmaceutical as the company producing tablet product is critical to make sure that the product safe for consumption. Not only impact the health of consumers, but also enable the company to decrease production cost. Pharmaceutical This research was done to control the quality of tablet product. Data collected is product defects of tablet at stripping process. The methodology uses six sigma approach. Finding of this research able to minimize the loss sales of product defects.